Perbandingan Letensi antara Jaringan Berbasis Fiber Optik dan Wireless pada Lingkungan Perkotaan - Fauzan Prasetyo Eka Putra; Pawitra Ramadhani; Waliyurrohman Waliyurrohman; Fahmi Abdillah (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
This research aims to analyze and compare the liveness between fiber optic and wireless based networks in an urban environment. Letency or data transmission delay time is an important indicator in assessing network performance, especially in applications that require high speed and stability such as video conferencing, streaming, and other real-time services. With a qualitative descriptive approach and a little experimentation, measurements were made using ping and traceroute methods in three different types of locations, namely dense residential areas, offices, and public spaces. Results show that fiber optic networks consistently have lower average latency, stability, and minimal fluctuation compared to wireless networks such as Wi-Fi, 4G, and 5G. Wireless shows advantages in flexibility but disadvantages in terms of signal stability, which is strongly influenced by user density and environmental conditions. User perception supports this data, with the majority of fiber network users satisfied with the speed and stability of the connection. In conclusion, optical fiber is technically superior, but synergy with wireless technology is needed to support mobility and broad access. Future research is recommended to involve more network parameters and analyze hybrid network scenarios.